Theme-Rheme Analysis in Probing Googleâ€™s Coercion Trespassing Userâ€™s Privacy; A Forensic Linguistics Research - Lesmana, Sabtra; Sawirman; Usman, Fajri (Center of Language and Cultural Studies [CLCS], 2022)
This research constitutes a mixture of multidisciplinary between linguistics with forensic. It represents the clause analysis through the use of theme-rheme in probing the user's privacy violations in Google's user privacy policy agreement: a forensic linguistics research. It is aimed to reveal and explain the violations conducted by Google to its user privacy which is implied through its text agreement by analyzing it with Theme and Rheme focus. This qualitative research is done by applying the documentation recording method in collecting data and the Hallidayâ€™s Systemic Functional Linguistics theory specifically theme-rheme. The result of the data is presented in the table analysis and in the form of descriptive interpretation. The result showed that Google build its clauses with the 4 types of theme construction. From 73 analyzed clauses, the dominantly built clause is the single constituent with marked theme where â€œWeâ€ is the mostly occurred subject with 31 occurences. Yet, Google applied unmarked theme mosty in their 38 clauses. With this dominant occurences of â€œWeâ€, Google construe its existence as the authority holders of the whole agreement. The researchers found that similar finite predicator appeared repeatedly such â€œcollectâ€ and â€œuseâ€ in building its clauses. These constitute Googleâ€™s strategy in order to force the userâ€™s permission to let Google freely access their privacy. In addition, the operation of the conjunction â€œAndâ€, extention, expansion and exemplificatory constituents represent the plentiful request of Google related to its userâ€™s information. Those summarized the violation conducted by Google to its userâ€™s privacy.